NIR-II Upconversion Photoluminescence of Er3+ Doped LiYF4 and NaY(Gd)F4 Core-Shell Nanoparticles - Feng, Qilong; Zheng, Wenjing; Pu, Jie; Chen, Qiaoli; Shao, Wei (Frontiers in Chemistry, 2021)
The availability of colloidal nano-materials with high efficiency, stability, and non-toxicity in the near infrared-II range is beneficial for biological diagnosis and therapy. Rare earth doped nanoparticles are ideal luminescent agents for bio-applications in the near infrared-II range due to the abundant energy level distribution. Among them, both excitation and emission range of Er3+ ions can be tuned into second biological window range. Herein, we report the synthesis of ∼15 nm LiYF4, NaYF4, and NaGdF4 nanoparticles doped with Er3+ ions and their core-shell structures. The luminescent properties are compared, showing that Er3+ ions with single-doped LiYF4 and NaYF4 nanoparticles generate stronger luminescence than Er3+ ions with doped NaGdF4, despite the difference in relative intensity at different regions. By epitaxial growth an inert homogeneous protective layer, the surface luminescence of the core-shell structure is further enhanced by about 5.1 times, 6.5 times, and 167.7 times for LiYF4, NaYF4, and NaGdF4, respectively. The excellent luminescence in both visible and NIR range of these core-shell nanoparticles makes them potential candidate for bio-applications.